IMPLEMENTASI PASAL 33 HURUF B PERATURAN PRESIDEN NOMOR 62 TAHUN 2023 TENTANG PERCEPATAN PELAKSANAAN REFORMA AGRARIA DI DESA SUMBER KLAMPOK, KECAMATAN GEROKGAK, KABUPATEN BULELENG - Putu Artadi,; Komang Febrinayanti Dantes; I Dewa Gede Herman Yudiawan (Jurnal Komunikasi Hukum, 2025)
This article examines the implementation of Article 33 letter b of Presidential Regulation Number 62 of 2023 concerning the Acceleration of Agrarian Reform in Sumberklampok Village, Gerokgak District, Buleleng Regency. The focus is on the land certification program for transmigrant residents and the obstacles faced by the National Land Agency. The research method used is empirical legal research with a descriptive qualitative approach. The results show that the implementation was carried out through the Agrarian Reform Task Force (GTRA), with 94 land title certificates successfully issued, while 14 plots of land still face barriers due to beneficiary conflicts and unclear land status. This article recommends strengthening interagency coordination and expediting the legal status determination of land as a solution.